Palmitoylation and membrane association of the stress axis regulated insert (STREX) controls BK channel regulation by protein kinase C - Zhou, Xiao-Bo; Dobrev, Dobromir; Wieland, Thomas (The journal of biological chemistry, 2012)
Large-conductance, calcium- and voltage-gated potassium (BK) channels play an important role in cellular excitability by controlling membrane potential and calcium influx. The stress axis-regulated exon (STREX) at splice site 2 inverts BK channel regulation by protein kinase A (PKA) from stimulatory to inhibitory. Here we show that palmitoylation of STREX controls BK channel regulation also by protein kinase C (PKC). In contrast to the 50% decrease of maximal channel activity by PKC in the insertless (ZERO) splice variant, STREX channels were completely resistant to PKC. STREX channel mutants in which Ser700, located between the two regulatory domains of K+ conductance (RCK) immediately downstream of the STREX insert, was replaced by the phosphomimetic amino acid glutamate (S700E) showed a ~50% decrease in maximal channel activity, whereas the S700A mutant retained its normal activity. BK channel inhibition by PKC, however, was effectively established when the palmitoylation-mediated membrane-anchor of the STREX insert was removed by either pharmacological inhibition of palmitoyl transferases or site-directed mutagenesis. These findings suggest that STREX confers a conformation on BK channels where PKC fails to phosphorylate and to inhibit channel activity. Importantly, PKA which inhibits channel activity by disassembling the STREX insert from the plasma membrane, allows PKC to further suppress the channel gating independent from voltage and calcium. Our results present an important example for the cross-talk between ion channel palmitoylation and phosphorylation in regulation of cellular excitability.